Representation of Nationalism in Local Media (Critical Discourse Analysis on Local Media Waspada Online) - Maulana Andinata Dalimunthe; Sofiari Ananda (Academic Solution Publisher, 2024)
The role of local media as an instrument of Nationalism representation has an important impact in shaping national identity at the regional and local levels. Local media has a closer coverage of the community and a deeper understanding of local culture, traditions, and values. This study aims to find out the representation of citizen nationalism in local online media Waspada Online. Representation of nationalism by local media can accommodate cultural diversity and its voices, appreciate differences, and strengthen unity in the context of Indonesia. Research on the role of local media in representing nationalism has a fundamental urgency in building a sense of nationhood and statehood. The research method used is the media discourse analysis method. Data collection techniques were text analysis and in-depth interviews. Research informants came from Waspada journalists, the Tourism Office, tourism observers, and Waspada online readers who were considered representative. Analysis includes data reduction, data presentation, conclusion drawing, and verification. The results showed that of the six news articles analyzed using the CDA technique, actors, namely public officials, dominated the majority. This represents that the context of nationalism tends to be constructed at an elitist level. However, there was one article where one of the political actors could distort the news content so that most of the framing that emerged was the community